The Dimensionality on the Mayor of Surakarta`S (2016-2021) Javanese Covid-19 Posters - Burhanudin, Hanif; Sumarlam, Sumarlam; Rakhmawati, Ani (Humaniora: Journal of Indonesia Culture and Society, 2021)
The research aimed to describe dimensions of the Mayor of Surakarta’s (2016-2021) Javanese COVID-19 posters. The research design was qualitative with Fairclough’s Critical Discourse Analysis (CDA) paradigm. The research data were the two Javanese COVID-19 posters retrieved from the Mayor of Surakarta’s (2016-2021) Instagram account. Data were analyzed in three stages: (1) Analyzing linguistically by paying attention to textual and linguistic elements, (2) Analyzing its discourse process, and (3) Analyzing by examining the sociocultural context. This research finds three dimensions: (1) textual dimension; those posters are constructed by the Javanese language with a persuasive-educative form. Also, there is a relationship between consumers and producers that are interwoven in power and cultural relations. (2) Discourse practice dimension, the process of production, distribution, and consumption, shows that the poster is produced and distributed directly by the ruling institution through social media and is intended to be consumed by Surakarta’s citizens. Also, there are intertextual refers to the central government regulations. (3) Socio-cultural dimension, three levels are found. Those three levels are the situational, institutional, and social levels, which show that the poster is influenced by pandemic situations and contexts beyond the language, such as Surakarta’s cultural context and social conditions. Based on these dimensionalities, the poster is functioned by the Mayor of Surakarta’s Institution to persuade, educate, andinfluence the citizen, also to respond to the COVID-19 situation.